How is the Mother Tongue Acquired - mansour fahim (Matn/Pizhūhī-i Adabī, 2000)
The ability of children lo communicate,  especially al the early stage of their lives, is quite remarkable.  When they are very young, they start  crying,  cooing ,  babbling and gradually begin lo send a great number  of messages, either  vocally or nonvocally, and  d't  the same  time they  receive even  more messages. When they are about J 2 months old,  they begin lo produce some of the speech sounds and even words they hear in their environment.  They produce  one word for one sentence which is known as "Holophrastic"  utterances. The number of words produced by children,  by about 17 to 18 months, have  remarkably multiplied,  and they  make specific attempts to make combination  of their produced  words in order to form two-word and even three-word "sentences". This new combination  of words are commonly reffered to as "telegraphic"  utterances. From the stge 11{ 211  month, onward the child will gradually increase the production of more and more words on the one hand,  and combine his two-and-three-word sentences on the other hand. When the child is about .1 years old, slhe  can easily understand  a surprising  quantity  of linguistic  behavior. Her/ his speech capacity grows so rapidly thats/he can have continual conversation  ass/he generates a  lot  of new structures,  though slhe does not know the real meaning  of the expressions slhe produces. Since the subject  matter  iS somehow  rather comprehensive, the  article  has  to he submitted  in  two parts.  the first part finishes  at  the  end  of "Stage  Three" -Eraly  Multi-  Word production period  (18-24  months  of age), and the second part starts from  "Stage  Four"  -Later Multi-  word production period (24-30 months rage)